The importance of the infection by human papillomavirus in patients of male sex - Mendonça, Márcio L.; Netto, Joaquim C.A. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Clinical, experimental and epidemic evidences demonstrate that the Human Papillomavirus (HPV) is sexually transmitted, with man being directlyinvolved in the epidemic chain of that virus as a reservoir and transmitter. The role of persistent infections by some genotypes of these viruses in theintraepithelial, cervical neoplasias, in the carcinogenesis of the cervix, and also in the carcinoma of the penis, is definitively established. So, by acting as “bearers” and/or “reservoirs” of an HPV oncogenic strain, man can be responsible for the increased risk of the cervix carcinoma, by frequentabsence of lesions visible at naked eye in the infected individual. This study describes the main diagnostic possibilities of the HPV in males, from thephysical exam to evaluation techniques by means of the molecular biology. The oncogenic inducing mechanisms that lead to oncogenesis by the HPV, and the cofactors associated to oncogenesis are also discussed.